2017
DOI: 10.21098/bemp.v20i1.723
|View full text |Cite
|
Sign up to set email alerts
|

Determinant of Efficiency of the Islamic Banking in Indonesia

Abstract: Dual banking system in Indonesia provides an excellent opportunity for the growth of Islamic banking industry in Indonesia. Islamic banking industry in Indonesia has improved in number of banks and branches but the performance of Islamic banks has decreased in recent years. This paper measures the efficiency of Islamic banking in Indonesia using the intermediation approach and the Data Envelopment Analysis (DEA) on quarterly reports of 10 Islamic Banks (BUS) and 15 Islamic Business Units (UUS). The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 3 publications
5
19
0
7
Order By: Relevance
“…These conditions must maintain in the following year. This result is not surprising because it agrees with previous research conducted by Widiarti et al (2015) and Hidayati et al (2017). The research finds that Bank of Sharia Mandiri is experiencing a relatively good trend of efficiency.…”
Section: Bank Of Bri Sharia Indonesiasupporting
confidence: 91%
“…These conditions must maintain in the following year. This result is not surprising because it agrees with previous research conducted by Widiarti et al (2015) and Hidayati et al (2017). The research finds that Bank of Sharia Mandiri is experiencing a relatively good trend of efficiency.…”
Section: Bank Of Bri Sharia Indonesiasupporting
confidence: 91%
“…Kamarudin et al (2016b) concluded that the impact of the financial crisis on the level of banking efficiency actually occurred after the crisis, not during a crisis, due to the time lag or time lapse until the impact begins to be felt in the financial and banking industries. The results are relevant to Hidayati et al (2017) that Islamic banks and Islamic business units in Indonesia did not function efficiently in its intermediation. Islamic commercial banks in Indonesia are able to optimize their resource inputs to produce outputs as an intermediary institution (Farandy et al, 2017).…”
Section: Discussionmentioning
confidence: 87%
“…However, Pambuko (2016) also observed the magnitude of the GDP (Gross Domestic Product) and inflation in which both of them have insignificant effect toward efficiency. Similarly, Hidayati et al (2017) found that CAR and financing products from SB have a positive influence on the efficiency, while in Third Parties Funds TPF) showed the reverse. In contrast, Firdaus & Hosen (2013) found that CAR, NPF, and the Number of Branches (NB) owned by SB negatively affect the value of efficiency, even though ROA, ROE (Return on Equity), and the value of assets hare positively associated.…”
Section: Introductionmentioning
confidence: 91%
“…In order to compete with conventional banks, SB need to improve and maintain their efficiency. Many studies emphasize that efficiency is important because it can be used as an indicator to assess the bank's ability to maintain performance as the agency in charge of collecting and distributing public funds (See, For example, Widiarti et al, 2015, Wheelock & Wilson, 1999, Hidayati et al, 2017, Muharam & Pusvitasari, 2007, Bisri, 2016, Subandi & Ghozali, 2014, and Weill, 2003. Moreover, efficiency can also be used as a measurement of banks' ability to optimize the output so that SB can provide benefits to customers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation